Efektivitas Strategi Pembelajaran Ropes dalam Meningkatkan Motivasi Belajar Peserta Didik pada Mata Pelajaran Sejarah - Agi Maruf Wijaya (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2022)
This study aimed to determine the effectiveness of the ROPES learning strategy in increasing students' learning motivation in learning history. This study used a qualitative and quantitative approach. The type of research design used in this research activity was classroom action research. The techniques used to collect data in this study include the main data collection techniques, namely: observation and test methods, while the supporting data collection techniques were interview and documentation methods. In this study, the data analysis used was quantitative data analysis and qualitative data analysis. Based on the results of the post-test and pre-test, it can be concluded that the ROPES learning strategy was effective in increasing students' learning motivation.